PEMBUATAN DAN UJI AKTIVITAS SEDIAAN UNGUENTA SCARLESS WOUND DENGAN EKSTRAK BINAHONG DAN ZAT AKTIF ASPIRIN - Maria Faustina Sari; Sri Hartati Yuliani (Sanata Dharma University, 2015)
Wound is a defect of skin caused by physical or thermal damage. The inflammatory phase in the wound healing usually causes scars. Aspirin is a nonsteroidal anti-inflammatory drug (NSAID) that has the ability to inhibit the activity of cyclooxygenase (COX) leading to reduced prostaglandin amount. Binahong (Anredera cordifolia) is one of the plants that is used as a wound healer. Binahong contains ascorbic acid which has an important role in collagen formation phase. In this study, binahong leaf extract ointment will be combined with aspirin to produce scarless wound ointment. The method used is a purely experimental method. The test method used is histopathology tests then processed by the method of calculating the area of collagen. The data are analyzed using T-test. The addition of aspirin in the preparation of wound healing ointment cant reduce scar formation allegedly with an incision method of white mice (Mus musculus) Swiss Webster. Statistically, the results showed that binahong ointment (UB) produces the least scar than ointment base (B), followed binahong-aspirin ointment (UBA), and aspirin ointment (UA).